Multi-dimensional Additive Manufacturing - Kirihara, Soshu; Nakata, Kazuhiro (Springer Singapore, 2021)
In this book, basic sciences and applied technologies in 3D printing and 2D coating-including 2D surface modulations on 3D printed objects-are described to explore and to image novel multidimensional additive manufacturing. Renowned researchers were selected from universities and national institutes as authors by the editorial board established in the Surface Modification Research and Technology Committee of the Japan Welding Engineering Society. The main readers of this book are expected to be graduate students, professional researchers, and engineers. Here, they can acquire abundant knowledge of digital design concepts and functional evaluations, enabling them practice material selection and process parameter optimization in novel additive manufacturing
Part I: Lithography -- 1. Selective Laser Melting -- 2. Laser Processing for Metals -- 3. Electron Beam Melting -- 4. Current Research and Development -- 5. Stereolithography -- Part II: Nano/Micro Lamination -- 6. Chemical Vapor Deposition -- 7. Aqueous Solution Process -- Part III: Coating and Deposition -- 8. Aerosol Deposition Method -- 9. Cold Sprayed Metal Coatings -- 10. Cold Spray Technique -- 11. Precursor Spray
Keywords: Tribology; Corrosion and anti-corrosives; Coatings; Manufactures; Aufsatzsammlung